Lower versus higher starting tacrolimus dosing in kidney transplant recipients. Issue 6 (23rd February 2022) - Chua, Justin C. M.; Mount, Peter F.; Lee, Darren
Abstract: Achieving therapeutic tacrolimus levels is an essential component of balancing immunosuppression in kidney transplantation. At our institution, the starting tacrolimus dose was reduced from .075 mg/kg BD (higher dose [HD]) to .050 mg/kg BD (lower dose [LD]), to better achieve our target level of 6–10 μg/L in the early posttransplant period. Kidney transplant recipients (KTRs) transplanted 1‐year before (HD: n  = 64) and after (LD: n  = 63) the starting dose reduction were retrospectively compared. Achieved tacrolimus levels were significantly lower in the LD group during the first 14 days posttransplant, but not at day 21 or day 28. A higher proportion of LD KTRs achieved therapeutic levels (day 1–3: 36.1% vs. 18.8%; day 4–7: 50.8% vs. 40.6%, day 8–14: 83.6% vs. 71.7%), while the HD KTRs were more likely to have supratherapeutic levels. Tacrolimus dose was significantly lower on day 5 compared to day 0 in the HD group but similar in the LD group. Rates of delayed graft function, posttransplant diabetes, and treated rejection at 6 months and graft outcomes at 3 years were all similar. Lowering the starting tacrolimus dose increased the proportion of KTRs achieving therapeutic range and minimized dose changes early posttransplant without an impact on clinical outcomes.